Testicular tumor in an infant: A case report - Boris Cachay Tello; José Antonio Arias Delgado; Fernando Jeancarlos Imán Izquierdo; Pamela Lopez Peña; José Luis Barrantes Ticlla; Rodrigo Alonso Fribourg Liendo; Juana del Valle-Mendoza; Wilmer Silva-Caso (Urology Case Reports)
Testicular tumors in the pediatric population represent between the 1 % and 2 % of all malignant neoplasms detected in children. We present the case of a 6-month-old male patient diagnosed with testicular teratoma. A left radical orchiectomy was performed at 8 months of age, and pathology report confirms prepubertal teratoma. At 3 years follow-up, the patient is asymptomatic and remains under medical vigilance. This case report highlights the importance of early diagnosis and appropriate treatment of testicular tumors in children, as well as continuous follow-up and medical vigilance to monitor the patient's long-term health to avoid recurrence or complications.